Motivasi Petani dalam Berusahatani Hortikultura di Desa Wisata Candikuning, Kecamatan Baturiti, Kabupaten Tabanan - RESTUTININGSIH, NI LUH PUTU; DIARTA, I KETUT SURYA; SUDARTA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Farmers’ Motivation in Horticultural Farming in Candikuning Tourism Village, Baturiti Subdistrict, Tabanan Regency Horticultural farming in tourism destination is supposedly influenced by motivation who are able to encourage themselves who are not included in farmer community to carry out holticultural farming activities in the Candikuning Tourism Village. The purpose of this study is to determine the level of farmers’ motivation who are not included in farmer community in terms of intrinsic and extrinsic aspect in Horticultural Farming in Candikuning Tourism Village. The results show that the level of farmers’ motivation falls into high category with an average score of 3.67 (73.44%) of the total maximum score. This is supported by the intrinsic motivation included in the high category with an average score of 3.91 (78.34%) of the total maximum score and extrinsic motivation included in the high category with an average score of 3.42 (68.53%) of the total maximum score. So that the level of farmers’ motivation in horticultural farming is high. The agricultural extension workers that assist the farming activity in Candikuning Village should counsel the farmers actively. The farmers should form a farmer’s forum in order to facilitate them to gain information about their farming activity. The agricultural extension workers should be able to give effect to the farmers, through the delivery of messages that agricultural traders Keywords: motivation, farmers, horticultural farming, Candikuning Tourism Village